The Effects of Mobile Payment Dimensions toward Continuance Intention in Surabaya - Sandra Yunita; Erna Andajani (Institut Teknologi Sepuluh Nopember, 2020)
The 4.0 industrial revolution allows people to make payments using mobile devices which is called mobile payment. Mobile payment users in Indonesia have enlarged a significant improvement in the last few years. However, the use of mobile payment in Indonesia has not dominated yet. Most of the payments that they use are ATM Transfers, debit cards, and internet banking. These indicate the lack of continuance intention in using a mobile payment. The aim of this study is to examine the effects of mobile payments dimension (mobility, customization, security, reputation), service quality toward continuance intention through trust, and also the effects of trust toward continuance intention through perceived risk. The data used in this study are obtained through a research questionnaire. Respondents in this study were 170 Go-Pay and OVO users domiciled in Surabaya who made transactions with Go-Pay and OVO at least twice in the last few months. The sampling method of this study was non-probability sampling. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method for statistical test. SEM analysis was carried out using the Analysis of Moment Structures (AMOS). The results of this study indicate that mobility and security have a significant positive effect on trust. On the other hand customization, reputation, and service quality do not affect trust. Trust has a significant positive effect on continuance intention and perceived risk. Meanwhile, the perceived risk made a significant negative effect on continuance intention.